Sibling spillover effects in school achievement - Cheti Nicoletti; Birgitta Rabe (University of Essex, Institute for Social and Economic Research (ISER), 2014)
We provide the first empirical evidence on direct sibling spillover effects in school achievement using English administrative data. Our identification strategy exploits the variation in school test scores across three subjects observed at age 11 and 16 and the variation in the composition of school mates between siblings. These two sources of variation have been separately used to identify school peer effects, but never in combination. By combining them we are able to identify a sibling spillover effect that is net of unobserved child, family and school characteristics shared by siblings. We find a modest spillover effect from the older sibling to the younger but not vice versa. This effect is considerably higher for siblings from deprived backgrounds, where sibling sharing of school knowledge might compensate for the lack of parental information.
Keywords: I22; I24; 330; family effects; peer effects; social interaction; education